2019
DOI: 10.33225/pec/19.77.379
|View full text |Cite
|
Sign up to set email alerts
|

On Perception of Computer Algebra Systems and Microsoft Excel by Engineering Students

Abstract: This research presents the analysis of image of the popular program packages: CAS (Computer Algebra Systems) Matlab, Mathcad, Mathematica, and the spreadsheet ‘Microsoft Excel’ among students of engineering specializations studying in Bauman Moscow State Technical University (BMSTU). The research has explored perception of program packages by all students (N=164), and by male students (N=110) and female students (N=54) separately. Image of the program packages, convenience of their interfaces, usage scenarios,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…In a recent study by Mezhennaya and Pugachev [14], the authors compared engineering students' perceptions regarding several mathematical software: Matlab, Mathematica and Excel. The study found that all the scientific packages considered can be used in education, under the condition that the policies for software usage are carefully implemented.…”
Section: University Mathematics Curriculummentioning
confidence: 99%
“…In a recent study by Mezhennaya and Pugachev [14], the authors compared engineering students' perceptions regarding several mathematical software: Matlab, Mathematica and Excel. The study found that all the scientific packages considered can be used in education, under the condition that the policies for software usage are carefully implemented.…”
Section: University Mathematics Curriculummentioning
confidence: 99%
“…The digitalization of education also manifests itself in taking tests using computers, online universities, and online courses [3]. Besides, educational tools are becoming increasingly digitized [4][5]. Another important aspect of the digitalization of education is the automation of routine education tasks, for example, checking homework assignments using digital technology.…”
Section: Introductionmentioning
confidence: 99%
“…This trend is expressed by taking tests using computers, online universities, and online courses [3]. Moreover, the digitization of educational tools is another critical trend [4][5].…”
Section: Introductionmentioning
confidence: 99%